2014
DOI: 10.1017/bec.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Brief Format of the Triple P-Positive Parenting Program: A Pilot Study With Indonesian Parents Residing in Australia

Abstract: Dissemination of evidence-based parenting programs in developing countries is warranted, but prior to dissemination, the cultural appropriateness of programs needs to be assessed. This study provides an evaluation of the level of acceptability among Indonesian parents and the efficacy of a brief parenting program, the Triple P-Positive Parenting seminar. Thirty Indonesian parents of children aged 2–12 years old residing in Australia participated in the study. A 90-minute Triple P seminar with minimal changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Morawska et al (2014) reported that the CAPES had satisfactory convergent and discriminant validity, as well as good internal consistencies (α = .74-.96) among Australian parents. The CAPES has been used in two intervention studies with Indonesian parents (Sumargi et al 2014(Sumargi et al , 2015a, the internal consistencies were reported to be good (α = .81, Sumargi et al 2014;α = .71-.94, Sumargi et al 2015a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morawska et al (2014) reported that the CAPES had satisfactory convergent and discriminant validity, as well as good internal consistencies (α = .74-.96) among Australian parents. The CAPES has been used in two intervention studies with Indonesian parents (Sumargi et al 2014(Sumargi et al , 2015a, the internal consistencies were reported to be good (α = .81, Sumargi et al 2014;α = .71-.94, Sumargi et al 2015a).…”
Section: Methodsmentioning
confidence: 99%
“…Further, due to a paucity of a validated child-outcome measures in Indonesia, the CAPES was used for testing the predictive validity of PAFAS. The CAPES has not been validated in Indonesian culture which may represent a limitation; however, the internal consistencies of the measure in two intervention studies with Indonesian samples of parents were good (Sumargi et al 2014(Sumargi et al , 2015a. Future studies should employ more robust procedures and include various parenting and child-outcome measures to further validate the Indonesian PAFAS.…”
Section: Limitationsmentioning
confidence: 99%
“…Significant decrease in children's conflict, an increase in closeness and positive relationships between parents and children and an increase in parental competence in childcare are side effects of this program (Breitkreuz et al, 2011;Morawska et al, 2011;Sumargi, Sofronoff and Morawska, 2014;Ashori et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The DDI's Corporal Punishment scale is designed to assess changes in specific, goal-directed behaviours (Straus & Fauchier, 2007). Studies that have found the Triple P seminars to be effective in reducing coercive parenting have used instruments that measure parenting styles, or global dimensions or categorisations, such as permissive discipline or authoritarian discipline (Sumargi et al, 2014; Sanders et al, 2009). Another explanation may be that parents may need longer than the 2-week assessment period post-intervention to implement other strategies learned.…”
Section: Discussionmentioning
confidence: 99%
“…Together with these findings, the present results might indicate that Level 2 Triple P is not sufficient to convince or enable parents to eliminate their use of physical and other punishments. They may require a more intensive program variant or more discussion time, examples of how to implement the strategies, or additional support (Sanders et al, 2008; Sumargi et al, 2014). Given that in two of the three seminars there is limited focus on teaching actual strategies, changes in seminar content may be required to achieve changes in parents’ behaviour.…”
Section: Discussionmentioning
confidence: 99%